2022
DOI: 10.2147/ccid.s379904
|View full text |Cite
|
Sign up to set email alerts
|

New Progress in Therapeutic Modalities of Striae Distensae

Abstract: Striae distensae (stretch marks/striae gravidarum) is one of the common cosmetic problems that can cause psychological distress and anxiety to patients due to its disfiguring damage, especially for women. The etiology of striae distensae is currently unknown, and risk factors include low maternal age, family history of stretch marks, excessive weight gain during pregnancy, and high neonatal weight. This article reviews the latest literature on the most commonly used, most popular, and novel treatment modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Research has primarily focused on combining different modalities, such as radiofrequency (RF), laser, platelet‐rich plasma (PRP), needling, and topical treatments, rather than specifically combining different types of lasers. Nevertheless, the evidence supports the potential of the combination approach in the treatment of SD 1,9 . Combined ablative and non‐ablative lasers have shown impressive results in some previous studies treating various skin conditions, but these studies used separate devices and required a split protocol 6 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Research has primarily focused on combining different modalities, such as radiofrequency (RF), laser, platelet‐rich plasma (PRP), needling, and topical treatments, rather than specifically combining different types of lasers. Nevertheless, the evidence supports the potential of the combination approach in the treatment of SD 1,9 . Combined ablative and non‐ablative lasers have shown impressive results in some previous studies treating various skin conditions, but these studies used separate devices and required a split protocol 6 .…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the evidence supports the potential of the combination approach in the treatment of SD. 1,9 Combined ablative and non-ablative lasers have shown impressive results in some previous studies treating various skin conditions, but these studies used separate devices and required a split protocol. 6 More recent studies have reported positive results with hybrid laser platforms, which combine both ablative and non-ablative lasers in a single protocol, for a variety of skin conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin lasers have improved, even more so after the development of fractional laser treatment, which is characterized by reepithelization due to the migration of viable cells from undamaged sites to the injury site [ 9 ]. Laser categories include non-ablative fractional laser, radiofrequency (RF), long pulsed Nd:YAG, fractional CO 2 laser, fractional bipolar RF, fractional ablative microplasma RF, and intense pulsed light (IPL) [ 13 , 14 ]. Laser therapy represents a great advance in treating stretch marks, specifically striae rubrae, since there is an increase in the vascularization of the lesions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%